Individual quality explains variation in reproductive success better than territory quality in a long-lived territorial raptor. - Jabi Zabala (Public Library of Science (PLoS), 2014)
Evolution by natural selection depends on the relationship between individual traits and fitness. Variation in individual fitness can result from habitat (territory) quality and individual variation. Individual quality and specialization can have a deep impact on fitness, yet in most studies on territorial species the quality of territory and individuals are confused. We aimed to determine if variation in breeding success is better explained by territories, individual quality or a combination of both. We analysed the number of fledglings and the breeding quality index (the difference between the number of fledglings of an individual/breeding pair and the average number of fledglings of the monitored territories in the same year) as part of a long term (16 years) peregrine falcon (Falco peregrinus) monitoring program with identification of individuals. Using individual and territory identities as correlates of quality, we built Generalised Linear Models with Mixed effects, in which random factors depicted different hypotheses for sources of variation (territory/individual quality) in the reproductive success of unique breeding pairs, males and females, and assessed their performance. Most evidence supported the hypothesis that variation in breeding success is explained by individual identity, particularly male identity, rather than territory. There is also some evidence for inter year variations in the breeding success of females and a territory effect in the case of males. We argue that, in territorial species, individual quality is a major source of variation in breeding success, often masked by territory. Future ecological and conservation studies on habitat use should consider and include the effect of individuals, in order to avoid misleading results.